Avaliação estocástica de afundamentos de tensão através de análise de curtos-circuitos deslizantes e banco de dados relacional - SILVA, Jucileno Silva e (Universidade Federal do Pará, 2012)
Nowadays, it is great the concern regarding the disturbances that affect electric power quality, especially voltage sags, due to the associated customer damages. This elapses from the growing presence of sensitive loads to theses disturbances, mainly in industrial processes. To evaluate the problem correctly, it is fundamental to have reliable estimates of the number and characteristics of the voltage sags that can affect certain load or process. In this context, this work proposes the implementation of a methodology for estimation of voltage sags that consists in calculate amplitude, duration and frequency of occurrence of the phenomenon, based on probabilistic study. In this study, the position of the fault along the lines is raffled, in order to best represent the randomness of occurrence of faults in the system. To evaluate the applicability of the implemented methodology, case studies are made using a real electric grid of a distribution utility in the north of Brazil (CELPA). The resultant analysis, allows to affirm that, the implemented methodology can be used efficiently to aid engineers in planning of electric systems and in diagnosing power quality related customer equipment problems.